Rumen effects of monensin in dry cow diets varying in energy density - B.F. Richards; J.A. Vasquez; K.L. Perfield; S.K. Kvidera; J.K. Drackley (Journal of Dairy Science, 2022)
ABSTRACT: Controversy has existed as to whether monensin will provide equal or differential benefits in a higher-energy, lower-roughage close-up diet versus a higher-roughage, lower-energy diet. Our objective was to determine the rumen effects of a controlled-energy, high-fiber diet balanced to meet but not greatly exceed energy requirements during the dry period or a traditional 2-group approach of higher-energy close-up diet. The effects of added monensin in each diet type were determined. Multiparous Holstein cows (n = 17) were fitted surgically with ruminal cannulas. During the first 4 wk of the dry period, all cows were fed a controlled-energy, high-fiber diet (CE) as a total mixed ration for ad libitum intake. During the last 3 wk before calving, half of the cows were switched to a higher-energy, close-up diet until calving (CU), whereas the other half continued to receive the CE diet. Within each dietary group, half of the cows received monensin (MON) supplementation in the diet (24.2 g/t of total dry matter) and half did not (CON). After calving, all cows received the same lactation diet containing monensin (15.4 g/t of dietary dry matter). At 14 d prepartum, dry matter intake was not different across treatments. The weight of rumen contents was greater for cows fed CE. Rumen liquid dilution rate, solids passage rate, pH, total volatile fatty acid (VFA) concentrations, molar proportions of acetate and propionate, and papillae length did not differ among diets. Butyrate percentage tended to be greater for cows fed CE. Postpartum, dry matter intake, mass of rumen contents, solids passage rate, pH, total VFA concentration, molar percentages of propionate and butyrate, and papillae length did not differ among treatments. Liquid dilution rate (16.6, 10.7, 16.0, and 18.2%/h for CE + CON, CE + MON, CU + CON, and CU + MON, respectively) was affected by a diet × monensin interaction. Cows on the CE + CON diet had a greater ruminal proportion of acetate than did cows fed CU + CON, whereas cows fed monensin on either diet were intermediate (diet × monensin interaction). Addition of MON to the CU diet decreased the proportion of propionate (diet × monensin interaction). Cows fed CE had greater mass of rumen contents before parturtition but the high inclusion of wheat straw in the CE diet did not negatively affect rumen papillae length. Monensin inclusion differentially affected liquid passage rate and VFA concentrations.